Assessment of pattern of adverse drug reactions with chemo-therapeutic drugs in a tertiary care hospital of Government Medical College Anantnag: a prospective observational study - Ismail, Sheikh Hanan; Jabeen, Asra; Nabi, Masrat; Chashoo, Nasreen; Magray, Sami (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Adverse drug reactions (ADRs) are a global problem. The high toxicity of chemo-therapeutic agents makes assessment of ADR's due to anti-cancer drugs essential. The present study is done with the aim to assess and evaluate the pattern of ADR's due to anti-cancer therapy in hospitalized patients and to analyse the causality and severity of these reactions. Methods: A prospective observational study was conducted in department of pharmacology after getting approval from institutional ethics committee, GMC Anantnag over a period of 1 year. Patients of either sex with age >18 years was included. Data was collected directly from admitted patients in the oncology department and also from their medical case files. Causality and severity of ADRs were assessed by using the WHO-UMC causality scale and modified Hartwig and Seigel severity scale, respectively. Results: A total of 982 ADRs were reported from 442 patients. Mean age of all patients was 37.49±11.88 years with 260 (58.82%) females and 182 (41.17%) males. Colorectal carcinoma (18.55%) was found to be the most common. Among 442 patients included in this study, 982 ADRs were recorded, with the most common being nausea/vomiting (n=166, 16.90%) followed by alopecia (n=142, 14.46%) and skin rashes (n=121, 12.32%). On causality assessment, as per WHO-UMC criteria 85.78% of the reactions were probable and 8.26% were possible. The severity of the reported reactions based on modified Hartwig and Siegel scale showed 742 (75.56%) ADRs to be mild, 227 (23.1%) ADRs to be moderate and 13 (1.32) to be severe. Conclusions: ADRs are most important causes of morbidity and mortality and increase the economic burden on patient and society. Management of ADRs beforehand will help in reducing the suffering of patients and increase compliance. ADR monitoring is the need of the hour especially in cancer patients in order to increase quality of life, and decrease morbidity and mortality. However, early detection of the ADRs may help to modify the doses or the drug regimen to minimize the adverse effects.